Value-added education and smoking uptake in schools: a cohort study. - Markham, W; Aveyard, P; Bisset, S; Lancashire, E; Bridle, C; Deakin, S (2008)
AIM: To show that schools achieving higher examination pass and lower truancy rates than expected, given that their pupil populations (high value-added schools) are associated with a lower incidence of smoking among pupils (13-14 years). DESIGN: Value-added scores for schools were derived from standardized residuals of two regression equations predicting separately the proportion of pupils passing high school diplomas and the half-days lost to truancy from the socio-economic and ethnic profiles of pupils. The risk of regular smoking at 1- and 2-year follow-up was examined in relation to the value-added score in a cohort of 8352 UK pupils. Random-effects logistic regression was used to adjust for baseline smoking status and other adolescent smoking risk factors. SETTING: A total of 52 schools, West Midlands, UK. PARTICIPANTS: Year 9 pupils aged 13-14 years (n = 8352) were followed-up after 1 year (n = 7444; 89.1% of original cohort) and 2 years (n = 6819; 84.6% of original cohort excluding pupils from two schools that dropped out). MEASUREMENTS: Regular smoking (at least one cigarette per week). FINDINGS: Schools with high value-added scores occurred throughout the socio-demographic spectrum. The odds ratio (95% confidence interval) for regular smoking for a 1 standard deviation increase in the value-added measure was 0.85 (0.73-0.99) at 1-year and 0.80 (0.71-0.91) at 2-year follow-ups. Baseline smoking status did not moderate this. CONCLUSIONS: Schools with high value-added scores are associated with lower incidence of smoking. Some schools appear to break the strong link between deprivation and smoking. Understanding the mechanisms could be of great public health significance.